High efficiency hybrid perovskite tandem solar cells - Liang, Ophelia Mu En (Nanyang Technological University, 2023)
Hybrid perovskite solar cells are a photovoltaic device that utilizes a perovskite-based material as the active layer for converting sunlight into electricity. These solar cells have gained a lot of attention in recent years due to their high power conversion efficiencies, easy fabrication, and low production costs. In this report design and simulation of the hybrid perovskite solar cell to achieve higher performance have been reported. The device structure has been optimized by taking the thickness and material used for each layer into account. Through the use of a simulation program named SCAPS-1D, this study compares the efficiency of perovskite solar cell with that of hybrid perovskite solar cell, and conducts numerical experimentation to achieve the highest efficiency possible.